Childhood Experiences Associated with Care for the Natural World: A Theoretical Framework for Empirical Results - Chawla, Louise (Children, Youth and Environments, 2007)
A growing literature shows that active care for the environment in adulthood is frequently associated with positive experiences of nature in childhood or adolescence, along with childhood role models who gave the natural world appreciative attention. This article offers a framework for understanding this finding, drawing on two bodies of theory: the ecological psychology of James Gibson, Eleanor Gibson and Edward Reed, and the attachment theories of John Bowlby and Donald Winnicott. It shows how these two bodies of theory complement each other, as interpersonal theories of attachment add an emotional dimension to the processes of encountering the world described by ecological psychologists. Based on a re-analysis of interviews with environmentalists in Norway and the United States, the article looks closely at remembered childhood interactions with influential role models.
Publisher: University of Cincinnati